RELATIONSHIP BETWEEN NEUROSCIENCE AND THE STUDY OF CRIMINAL DOGMATICS AND ITS IMPORTANCE IN DETERMINING EVENTUAL MALICE AND GUILT WITH REPRESENTATION (2023)
The important advances made by neuroscience during the last decades have led to the rethinking of theories in different fields of knowledge, since this has allowed the creation of sophisticated technologies that allow obtaining images not only of the brain, but also of the neuronal functioning in the central nervous system, which makes it possible to establish whether a person acts with free will or not, or whether that person is really aware of the acts he performs in his daily life. This is of superlative importance for criminal dogmatic and for the theory of crime, especially when trying to determine whether a subject acts with intent or with recklessness at the time of performing an action that produces a typical result, which makes it possible to consider the idea of using neuroscience as expert evidence for criminal proceedings, closely following the requirements established in article 422 of Law 906 of 2004.